A possible method to predict response to non-pharmacological insomnia therapy. - Campana, L; Clifford, G; Trinder, J; Pittman, S; Malhotra, A (2011)
STUDY OBJECTIVES: To determine if electrocardiographic parameters are predictive of response to non-pharmacological insomnia therapy. DESIGN: Secondary analysis of heart rate parameters from a double blind, randomized, sham-controlled trial at multiple study sites. SETTING: Six sites in the United States were used for the data collection. PARTICIPANTS: One hundred ninety-eight healthy subjects with no sleep disorders. INTERVENTIONS: Subjects were studied on 2 consecutive nights, a baseline night and a therapy night. On the therapy night, subjects were phase advanced 4 h and randomized to receive either sham or vestibular stimulation, an experimental therapy for insomnia. MEASUREMENTS AND RESULTS: ECG data were recorded and analyzed for the 5-min periods preceding and following sleep onset. Analyses were conducted on those who did and did not respond to therapy, as defined by latency from bedtime to persistent sleep (LPS). Responders to therapy were found to have higher low-frequency (LF) power at baseline during wakefulness than non-responders, and responders had higher high-frequency (HF) power during therapy than non-responders on therapy. Furthermore, responders > 35 y had elevated LF power at baseline than non-responders > 35 y (p < 0.05). No differences were seen in the sham group in identical analyses, ruling out a nonspecific effect of sleep onset. CONCLUSIONS: Heart rate variability analyses indicate that differences exist between those who respond to insomnia therapy and those that do not, particularly in an older subset of subjects. Further research into the use of ECG and other physiological parameters to stratify response to therapeutic interventions is warranted.